New Hermeneutic, New Homiletic, and New Directions: An U.S. – North American Perspective (Homiletic, 2010)
In the ongoing conversation between North American and European hermeneutics and homiletics, this essay summarizes key influences of the New Hermeneutic on the New Homiletic and gives particular attention to an area of ongoing interest and concern, the “turn to the listener.” The final section suggests questions related to current trends in homiletics and areas in need of further development. This essay is a modified version of a book chapter based on a lecture given at the International Bugenhagen Symposium in Pullach, Germany, in October 2009. The book bears the same title as the theme of the symposium: Bibelwort und Kanzelsprache http://www.eva-leipzig.de/product_info.php?info=p2944_Bibelwort-und-Kanzelsprache.html